علاقته قلق الاختبار بالدافعية للإنجاز دراسة ميدانية لدى تلاميذ المرحلة البكالوريا من التعليم الثانوي بمدينة ورقلة - غزال، نعيمة; بن زاهي، منصور (جامعة قاصدي مرباح - ورقلة, 2014)
تهدف الدراسة الحالية إلى الكشف عن العلاقة الممكنة بين كل من قلق الامتحان والدافعية للإنجاز لدى عينة مـن تلاميـذ مرحلة التعليم الثانوي بمدينة ورقلة، كما هدفت إلى تفحص الفروق الممكن قيامها بين كل من الذكور والاناث و التخصص العلمي والأدبي وتمثل التساؤل الرئيسي في: هل توجد علاقة بين قلق الامتحان والدافعية للإنجاز لدى التلاميذ عينة الدراسة. وتمثلت عينة الدراسة الأساسية في تلاميذ السنة الثالثة ثانوي ببعض ثانويات مدينة ورقلة وقـد تـم اختيارهـا بطريقـة عشوائية عرضية، بلغ عددها 120 طالب وطالبة من السنة الثالثة ثانوي علوم وأداب وقد تم تطبيق استبيانين بعد التأكد من صدقهما وثباتهما يقيس الأول منهما قلق الامتحان، وقد تم في بنائه بالاستبيان الـذي أعده "نبيل الزهار" لقياس نفس الغرض، حيث تم اقتباس بعض الفقرات منه وتعديل بعض الفقرات الأخـرى، ويقـيس الاسـتبيان الثاني الدافعية للإنجاز وهو من تصميم هرمنز سنة 1971 وبعد المعالجة الاحصائية باستخدام البرنامج الاحصائي SPSS النسخة 18 توصلت الدراسة إلى النتائج التالية: عدم وجود علاقة بين قلق الامتحان والدافعية للإنجاز لدى التلاميذ عينة الدراسة كما توصلت إلى عدم وجود فروق ذات دلالة إحصائية في مستوى قلق الامتحان لدى التلاميذ عينة الدراسة تبعا لمتغير كل من الجنس والتخصص وقد نوقشت النتائج المتوصل إليها في ضوء الدراسات السابقة والجانب النظري واختتمت ببعض المقترحات The present study aims to detect the possible relationship between each of the test anxiety and motivation to accomplish in a sample of secondary school pupils in Ouargla , also aimed to examine its possible differences between both males and females and specialization of scientific and literary concern in test anxiety. The main question in : Is there a relationship between test anxiety and achievement motivation among students study sample . The basic study sample consisted of the third year of secondary school pupils in some secondary schools in the city of Ouargla and has been selected at random cross , numbered 120 students from the third year of secondary school of scientific and literary class. It has been applied to two questionnaires after confirming their validity and constancy, the first one of them measures the test anxiety, and it has been in its construction with the questionnaire which prepared by , " Nabil al-Zahar, " to measure the same purpose , which borrowed some paragraphs from it and modifyed some of other paragraphs , and the second questionnaire measures the motivation to accomplish which is a design of Hrmenz in 1971. After the statistic treatment using the SPSS statistical software version 18, the study found the following results: There is no relationship between test anxiety and achievement motivation among students of the study sample. It also found a lack of statistically significant differences in the level of test anxiety among students in the study sample depending on the variable of sex and specialization. The results obtained were discussed of previous studies and the theoretical side and concluded with some suggestions
Keywords: قلق الاختبارات -- علم النفس التربوي -- الدافعية للإنجاز -- الدافعية للتعلم -- الفروق الفردية -- التعليم الثانوي -- طلاب المدارس الثانوية -- ورقلة، الجزائر